2021
DOI: 10.1111/ejed.12433
|View full text |Cite
|
Sign up to set email alerts
|

Motives for dropping out from higher education—An analysis of bachelor's degree students in Germany

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 25 publications
1
23
0
6
Order By: Relevance
“…Motives for dropping out of college have been found to be cumulative and interdependent (Tinto, 1988;Heublein et al, 2017;Hartl et al, 2022). However, a recent study using NEPS data could not confirm significant differences in dropout motives between students from homes with lower academic background levels and their counterparts from families with more advanced academic backgrounds; still, descriptive results pointed to the direction that they were more prone to drop out for financial reasons (Behr et al, 2021).…”
Section: Study Satisfaction and Dropout Intentionsmentioning
confidence: 77%
“…Motives for dropping out of college have been found to be cumulative and interdependent (Tinto, 1988;Heublein et al, 2017;Hartl et al, 2022). However, a recent study using NEPS data could not confirm significant differences in dropout motives between students from homes with lower academic background levels and their counterparts from families with more advanced academic backgrounds; still, descriptive results pointed to the direction that they were more prone to drop out for financial reasons (Behr et al, 2021).…”
Section: Study Satisfaction and Dropout Intentionsmentioning
confidence: 77%
“…In this case, universities might be better of adjusting their strategy based on students' intentions and known reasons for why these intentions occur. Still, it is worth mentioning that external factors (e.g., work, child care, illness, finances) are also responsible for students' attrition (Bean, 1985;Bean and Metzner, 1985;Leveson et al, 2013;Hovdhaugen, 2015;Behr et al, 2021). For example, Behr et al (2021) identified a separate cluster of students who left university for personal (e.g., illness, stay abroad) or family (e.g., child care) reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it is worth mentioning that external factors (e.g., work, child care, illness, finances) are also responsible for students' attrition (Bean, 1985;Bean and Metzner, 1985;Leveson et al, 2013;Hovdhaugen, 2015;Behr et al, 2021). For example, Behr et al (2021) identified a separate cluster of students who left university for personal (e.g., illness, stay abroad) or family (e.g., child care) reasons. Family or personal reasons were rarely decisive for dropping out and were reported by a small proportion of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Para identificar las variables definitivas se utilizan herramientas estadísticas como el análisis de componente principales (FÉNYES; MOHÁCSI; PALLAY, 2021) y el de correlación (HERNÁNDEZ et al, 2018). Mediante clustering jerárquico aglomerativo (BEHR et al, 2021) se generan grupos de observación con un orden de prioridad, a partir de lo cual se definen los distintos perfiles de estudiantes. Con el método de conjuntos aproximados (BOUZAYANE; SAAD, 2017), se obtienen las reglas de decisión que permiten caracterizar los distintos conjuntos de alumnos.…”
Section: Modelounclassified
“…Se realiza un estudio cuantitativo de tipo exploratorio y descriptivo, basado en la aplicación de la metodología CRISP-DM (CHAPMAN et al, 1999) a la problemática de la deserción universitaria, mediante el Análisis de Componentes Principales (ACP) (FÉNYES; MOHÁCSI; PALLAY, 2021), Clustering Jerárquico Aglomerativo (CJA) (BEHR et al, 2021) y Conjuntos Aproximados (CA) (BOUZAYANE; SAAD, 2017).…”
Section: Metodologíaunclassified